A Blynk Controlled Solar Powered Golf Grass Cutter - Mohd Nor, Muhamad Fairus; Muhammad Soomro, Dur (Evolution in Electrical and Electronic Engineering, 2023)
The Internet of Things (IoT) has the potential to revolutionize the way golf courses grasses are maintained. One of the applications is the use of a smart grass cutter, which can be controlled remotely using a mobile device. This project describes the development of an IoT based smart grass cutter for golf course using the Blynk platform. The system includes a solar panel, a battery, a charge controller, a microcontroller, and a motor for cutting the grass. The microcontroller is connected to the Blynk platform, which allows for remote control and monitoring of the grass cutter. The system also includes a user interface access through the Blynk app, which allows for easy control and monitoring of the grass cutter. The system also includes a power management circuit that manages the power from the solar panel and the battery. The system has been tested and found to be effective in maintaining the grass of a golf course. This system can be a cost-effective, eco-friendly solution and can be easily scaled to other similar applications.